2019
DOI: 10.1177/0885066619871432
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Management in Pediatric Patients Undergoing Cardiac Surgery: Where Are We Heading?

Abstract: Objectives: Adequate postoperative pain management is crucial in pediatric patients undergoing cardiac surgery because pain can lead to devastating short- and long-term consequences. This review discusses the limitations of current postoperative pain assessment and management in children after cardiac surgery, the obstacles to providing optimal treatment, and concepts to consider that may overcome these barriers. Data Source: MEDLINE and PubMed. Conclusions: Effective pain management in infants and young child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
0
10
1
Order By: Relevance
“…4 It is suggested that arterial hypotension in patients undergoing ESPB is due to a sympathetic block by diffusion of the local anesthetic towards the anterior region through the costotransverse foramen, penetrating the thoracic paravertebral space generating blockage of the spinal branches and sympathetic fibers. 17 However, studies such as Kaushal et al 12 and our study did not report hemodynamic changes in patients with ESPB during the first 24 hours ( Table S1 ).…”
Section: Discussioncontrasting
confidence: 54%
“…4 It is suggested that arterial hypotension in patients undergoing ESPB is due to a sympathetic block by diffusion of the local anesthetic towards the anterior region through the costotransverse foramen, penetrating the thoracic paravertebral space generating blockage of the spinal branches and sympathetic fibers. 17 However, studies such as Kaushal et al 12 and our study did not report hemodynamic changes in patients with ESPB during the first 24 hours ( Table S1 ).…”
Section: Discussioncontrasting
confidence: 54%
“…Strategies should also be considered for development of less costly objective pain assessment tools. 5…”
Section: Moderate Strongmentioning
confidence: 99%
“…Pain management should be adjusted for individual experience of pain and reaction to interventions including undertreatment and overtreatment. 5…”
Section: Very Low Strongmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6 Additionally, the use of opioids in neonates and infants has been associated with long-term neurodevelopmental effects. 7,8 Following cardiac surgery and in response to validated pain and sedation scores, additional morphine doses may often be required. 2,9 An important question is whether a morphine concentration can be identified above which the probability of side effects (eg, oversedation) increases.…”
mentioning
confidence: 99%